2015
DOI: 10.1049/iet-gtd.2014.0169
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the sympathetic tripping problem in power systems with large penetrations of distributed generation

Abstract: This paper contains an investigation into sympathetic tripping -the undesirable disconnection of Distributed Generators (DGs) (in accordance with the recently-introduced G83/2 undervoltage protection) when a network fault occurs in the vicinity of the DG and is not cleared quickly enough by the network protection (i.e. before the DG's undervoltage protection operates). An evaluation of the severity of and proposal of solutions to the problem of sympathetic tripping on a typical UK distribution power network is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
40
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(41 citation statements)
references
References 13 publications
0
40
0
1
Order By: Relevance
“…Current dip: as shown by others [11] via experiments, the current output from the converter may experience an initial temporary "dip" in output immediately following a fault.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Current dip: as shown by others [11] via experiments, the current output from the converter may experience an initial temporary "dip" in output immediately following a fault.…”
mentioning
confidence: 86%
“…Synchronous machines may provide fault currents of 5-7 times larger than rated current immediately following close-up short circuits. However, the fault current provided by a converter-interfaced source may only be 1-2 times rated current [9] [10], and in some cases, under severe voltage depressions, some converters may not even be capable of providing rated current [11].…”
Section: Converter Fault Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence a great number of distributed low power sources have been connected to the LV grid in the last years, leading in some case to grid stability problem such as: transformer reverse power flow, voltage rise, unexpected islanding operations, sympathetic tripping, etc. [1], [2].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the studies in [41][42][43][44][45][46][47] suggested the adaptive protection scheme considering several types of relays (distance relays, OCRs, etc. ), also considering grid-connected and islanded mode of operations.…”
mentioning
confidence: 99%